Silo: Exploiting JavaScript and DOM Storage for Faster Page Loads - Mickens, James (Proceedings of WebApps, 2010)
A modern web page contains many objects, and fetching these objects requires many network round trips—establishing each HTTP connection requires a TCP handshake, and each HTTP request/response pair requires at least one round trip. To decrease a page’s load time, designers try to minimize the number of HTTP requests needed to fetch the constituent objects. A common strategy is to inline the page’s JavaScript and CSS files instead of using external links (and thus separate HTTP fetches). Unfortunately, browsers only cache externally named objects, so inlining trades fewer HTTP requests now for greater bandwidth consumption later if a user revisits a page and must refetch uncacheable files. Our new system, called Silo, leverages JavaScript and DOM storage to reduce both the number of HTTP requests and the bandwidth required to construct a page. DOM storage allows a web page to maintain a key-value database on a client machine. A Silo-enabled page uses this local storage as an LBFS-style chunkstore. When a browser requests a Silo-enabled page, the server returns a small JavaScript shim which sends the ids of locally available chunks to the server. The server responds with a list of the chunks in the inlined page, and the raw data for chunks missing on the client. Like standard inlining, Silo reduces the number of HTTP requests; however, it facilitates finer-grained caching, since each chunk corresponds to a small piece of JavaScript or CSS. The client-side portion of Silo is written in standard JavaScript, so it runs on unmodified browsers and does not require users to install special plug-ins.